Exploring Ethnomathematics in Junior High Schools: Indonesia's Contribution and Research Clusters in Enhancing 21st Century Skills - Ardhya Pramesthi Regita Iriandre; Swasti Maharani; Darmadi Darmadi; Hendrisa Rizqie Romandoni (STAI Hubbulwathan Duri, 2025)
Ethnomathematics is a field that integrates mathematical concepts with cultural elements. At the junior secondary school level, it offers significant benefits by contextualizing mathematics through students’ cultural backgrounds and traditions. This study explores the application of ethnomathematics in junior high schools, focusing on Indonesia’s contribution to this field and identifying key research clusters. A bibliometric analysis design was employed using data sourced from Dimensions AI. A total of 645 publications were analyzed using VOSviewer and Microsoft Excel. The analysis followed a descriptive qualitative approach to identify trends and patterns in the literature. Findings reveal that Indonesia is the leading contributor to ethnomathematics research at the junior secondary level, indicating its dominant role in this domain. Nineteen research clusters were identified, with primary themes including technology integration, ethnomathematics, batik, mathematical communication, assessment, mathematical concepts, and learning media. These clusters highlight a growing focus on technology-based learning media aimed at enhancing 21st-century skills. The results demonstrate that ethnomathematics in Indonesia is not only culturally relevant but also increasingly aligned with digital innovations in education. The integration of local culture with technology-based media fosters critical skills such as computational thinking and problem-solving. This study concludes that Indonesia plays a significant role in advancing ethnomathematics at the junior high school level, particularly through the development of technology-enhanced learning media that support 21st-century skill development.